Understanding the performance of profiled composite walls in fire. (1st May 2023) - Le, Quang X.; Dao, Vinh T.N.; Torero, Jose L.
Abstract: To understand the performance of structural elements subject to one-side heating, the combined effects of temperature and temperature gradient (or the non-uniform temperature increase) must be accurately considered in developing structural performance models. However, due to insufficient consideration of such effects, the direct application of current understanding of general structural performance at high temperature on structural elements like profiled composite walls (PCWs) seems insufficient because of the complex role that the different materials can have in the presence of significant temperature gradients. Therefore, more research is needed to understand the performance of these structural elements when subjected to temperature increase and temperature gradients. Only then, the performance of PCWs at high temperature can be appropriately addressed. This paper presents and verifies a structural performance model that can be used to analyse the performance of PCWs subjected to combined thermal and mechanical loadings. First, details of an analytical study are presented, including thermal stress calculation within inhomogeneous and composite cross-section by fully considering the effects of non-uniform stiffness, non-linear temperature gradient, shifting of the neutral axis, and the coupling effects between stress and thermal expansion. Second, previously published experimental results into the performance of PCWs subjected to combined mechanical loading and one-side heating are then used to verify the newly-developed analytical model. It is also argued that the methodology for stress and curvature calculation developed in this study can be used to assess the performance of any structural elements (PCWs included) subjected to one-side heating. (244 words). Highlights: Discuss limitations of the current structural performance model at high temperature. Highlight the importance of non-uniform temperature effects in developing a model. Establish a structural model for profiled composite walls at high temperature. Discuss the implications of the developed methodology for any structural elements.